ANALISIS PENGHAMBAT PENYELESAIAN STUDI MAHASISWA S1 PROGRAM STUDI PENDIDIKAN TEKNIK MESIN JURUSAN PENDIDIKAN TEKNIK DAN KEJURUAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET SURAKARTA - Kusnendar, Febriyanto (Jurnal Nosel, 2013)
The purpose of the research is to acquire knowledge about the internal factors and external factors are a barrier to completion of the study in thesis writing student S1 in PTM JPTK UNS Surakarta. The source in this research are all students Mechanical Engineering Education JPTK FKIP UNS Surakarta class of 2006, 2007, and 2008. The sample is taken by using sampling purposive technique. The sample in this research are students Mechanical Engineering Education JPTK FKIP UNS Surakarta class of 2006, 2007, and 2008 which take courses thesis. The most dominant factor that inhibits completion of studies students PTM S1 JPTK FKIP UNS Surakarta, among others: (1) Internal factors is health factors, fatigue factors, and psychological factors. (2) External factors is guidance by professors factors, family factors, friends factors, student reference factors, and administrative thesis factors.